INSTITUTIONAL RESEARCH REVIEW & ETHICS BOARD APPROVAL: A NECESSITY FOR PUBLICATION AND INSTITUTIONAL PERCEPTION - Ahmed, Mian Saad (Journal of Postgraduate Medical Institute, 2022)
Institutional Review Boards (IRBs) or research ethics board of an institute is meant to provide safety and protection to all the concerns being raised in human and animal research.1 These boards are meant to cover wide range of ethical concerns which includes respecting autonomy, consent, confidentiality, beneficence, non-maleficence, justice and other such concepts initially raised in the verdict of Nuremberg (United States) and then covered in declaration of Helsinki and Council of International Organizations of Medical Scientists (CIOMS).2-5 Since then, such research committees are continuously being evolved from national to institutional levels with certain Terms of References (ToRs) to regulate the ethical aspects in research conduction. One must understand here, the responsibility of the institutions, colleges, and universities to curb the menace of unethical research and promote research integrity. It is the institutions which provide clean chit to the authors/investigators for conducting ethical research, while its practise during the research and maintaining integrity is something that remains unaddressed. Importantly, concerns about knowledge regarding ethics in research among the members of such boards, the number of functional ethics/review boards in an institute, and number of meetings conducted & recorded by the board annually is something which always raises doubts. It is presumed that a common practise is being adopted by many boards, wherein the Chairperson or Secretary of such board issues approvals without scheduling any meeting or analysing the proposals. Approval of such unethical research might have lethal outcomes for the research participants as has happened in the past, wherein conduction of studies without following ethical concerns had fatal outcomes.3 Accountability, and regularisation of ethical boards is a dire need in order to uplift research from an ethical perspective. In the United States of America, Office for Human Research Protections (OHRP) is one such department to overview the ethical conduction of research for a better outcome.6 In a study conducted on 313 protocols submitted to OHRP, only 47.1% of protocols were reviewed by full boards.6 In Pakistan, National Bioethics Committee (NBC) is the designated authority to look after ethical research, but institutions must also prioritise their role towards ethical research and ensuring research integrity. Proper training of members by different recognised certificate courses can be one solution. Courses like Certificate of Medical Editing or Journalism or biomedical ethics can play a pivotal role in teaching basic concepts of ethical research. In addition, proper ToRs, scheduling of meetings, records of approvals along with follow up monitoring and a functional regulating body are some other things which would help and promote ethics in research. The role of investigators, writers, and authors is another important pillar in the whole process of maintaining the ethics for research in humans. Mostly, the investigators are unaware of the Ethics/Review Board approval part of the study.7,8 Here, the knowledge of ethics among investigators is yet to be assessed, as it is believed that many are not fully aware of issues related to research integrity in this region.8 The investigators’ only concern is getting an ethical board approval for publication, which is a step made mandatory by the journals. The board on the other hand, merely check the words “ethical considerations will be met” written in the methodology and grants the approval. This situation obviously calls for remedial steps, wherein it is the responsibility of Medical Colleges, Institutions, & Universities to incorporate these basic principles of research ethics in the curriculum of the undergraduate and postgraduates. Regular workshops, Continuing Medical Education (CME), and refresher courses addressing these concerns are the need of the day for the investigators. This is one means through which investigators can be guided and equipped with important principles of ethical research and research integrity. Lastly, on part of journals, majority of whom, just ask for the Ethics/Review Board approval certificate as a pre-requisite.7 The concerns regarding the knowledge of ethical research among editors and its representation on the website of many journals is yet to be explored properly. It is pertinent to add and appreciate that in the past, it was due to persistent pressure by different journals and the input by Pakistan Association of Medical Editors, in this context that made institutions formulate Ethical/Review Boards.9 Policies published by Higher Education Commission (HEC) are also a source of guidance towards better research outcomes.10 Moreover, continuous training and refresher courses for the editorial board can also be a means to spread knowledge regarding ethical research and uplift research integrity. Nonetheless, research without ethics is not only meaningless but also more importantly, an unprincipled thing to attempt. The role of institutional bodies, investigators and journals along with their editorial board is irrefutable in promoting ethics in research, and should be appreciated at all levels.